The diagnostic and predictive value of ultrasonography in congenital diaphragmatic hernia - Liu, Qin; Ren, Hongyan; Wang, Mingxue; Feng, Zhong; Ma, Lishuang (Frontiers in Pediatrics, 2026)
ObjectiveThe current diagnostic and prognostic assessment of congenital diaphragmatic hernia (CDH) in neonates remains challenging. This study aimed to evaluate the utility of neonatal ultrasonography in the diagnosis and prognostic prediction of CDH in infants.Materials and methodsA retrospective analysis was conducted on clinical data from 152 infants diagnosed with CDH and admitted to the Department of Neonatal Surgery at Children's Hospital between 2017 and 2023. The cohort included 86 (56.6%) males and 66 (43.4%) females. Multivariate logistic regression was employed to identify factors associated with CDH prognosis. Receiver operating characteristic (ROC) curve analysis was performed to assess the predictive value of significant ultrasonographic indicators.ResultsMultivariate logistic regression identified four factors as significant predictors of mortality: diaphragmatic defect length >4 cm [odds ratio [OR] = 2.41, 95% confidence interval [CI]: 1.08–10.58], the presence of hepatic herniation (OR = 2.61, 95% CI: 1.16–5.87), absence of a hernial sac (OR = 4.86, 95% CI: 2.00–11.76), and concomitant lung ultrasound abnormalities (OR = 10.86, 95% CI: 1.28–21.85). The combination of these four parameters demonstrated strong predictive performance for mortality, with an area under the ROC curve of 0.860 (95% CI: 0.786–0.935).ConclusionDiaphragmatic defect length, hepatic herniation, hernial sac status, and lung ultrasound findings serve as valuable prognostic indicators in infants with CDH. Integrating these four parameters enhances prognostic accuracy and may support clinical decision-making.